Some aspects of Tropical meteorology with special reference to the Indian weather-An examination of Malurkar's concepts regarding them - DESAI, B.N. (MAUSAM, 1951)
In this article an examination has been made of Malurkar’s concepts regarding some aspects of tropical meteorology discussed in a series of notes published by him.